2015
DOI: 10.1073/pnas.1510077112
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-dependent tRNA halves enhance cell proliferation in breast and prostate cancers

Abstract: Sex hormones and their receptors play critical roles in the development and progression of the breast and prostate cancers. Here we report that a novel type of transfer RNA (tRNA)-derived small RNA, termed Sex HOrmone-dependent TRNA-derived RNAs (SHOTRNAs), are specifically and abundantly expressed in estrogen receptor (ER)-positive breast cancer and androgen receptor (AR)-positive prostate cancer cell lines. SHOT-RNAs are not abundantly present in ER − breast cancer, AR − prostate cancer, or other examined ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
480
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(491 citation statements)
references
References 53 publications
10
480
0
1
Order By: Relevance
“…Interestingly, when the tsRNA expression profile of breast cell lines was compared with that of prostate cell lines, ts-66 was always dysregulated: It was down-regulated in breast cancer cell lines but was up-regulated in the prostate AR − late-stage cell line compared with AR + early-stage and normal cells. Because tRNA halves and piRNAs were recently shown to be involved in hormone response in breast and prostate cancer (32,33), it is possible that tsRNAs also may be implicated in the response to sex hormones in hormone-related cancers. Last, we found a signature of 10 tsRNAs dysregulated in ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when the tsRNA expression profile of breast cell lines was compared with that of prostate cell lines, ts-66 was always dysregulated: It was down-regulated in breast cancer cell lines but was up-regulated in the prostate AR − late-stage cell line compared with AR + early-stage and normal cells. Because tRNA halves and piRNAs were recently shown to be involved in hormone response in breast and prostate cancer (32,33), it is possible that tsRNAs also may be implicated in the response to sex hormones in hormone-related cancers. Last, we found a signature of 10 tsRNAs dysregulated in ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…S1A). As many studies have reported novel functions of tRNAs or tRFs in cell proliferation or apoptosis, 5-7 , 10 , 11 , 28 , 29 we wondered whether the overexpression of these tRNAs would affect any cell phenotypes. Interestingly, the overexpression of tRNAs enhanced cell proliferation, based on [ 3 H]thymidine incorporation and cell number count; tRNA Leu CAG was found to show the most significant effects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As many studies have suggested different functions of tRFs, 8 , 9 , 11 , 28 , 36 , 37 we performed northern blotting to check whether the overexpression of tRNA Leu would generate corresponding fragments. We used 30-bp radioactive probes to detect the 3 mature isoacceptors of tRNA Leu as well as their 3′ and 5′ end-derived fragments.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular and molecular studies have shown that sex steroid hormones act on genes expression by which can control apoptosis in target cells. [8] Human colon cancer cells are also affected by sex steroid hormones. In vitro and in vivo studies have revealed that sex steroid hormone including progestins have pivotal role in proliferation of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%